2020
DOI: 10.3390/nu12092639
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-Cryptoxanthin and α-Carotene Have Greater Apparent Bioavailability Than β-Carotene in Subjects from Countries with Different Dietary Patterns

Abstract: β-carotene, α-carotene and β-cryptoxanthin are greater contributors to vitamin A intake than retinol in the human diet for most people around the world. Their contribution depends on several factors, including bioavailability and capacity of conversion into retinol. There is an increasing body of research showing that the use of retinol activity equivalents or retinol equivalents could lead to the underestimation of the contribution of β-cryptoxanthin and of α-carotene. The aim is to assess their apparent bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…The carotenoid concentration in faeces has been used as a non-invasive approach to evaluate carotenoid bioavailability [ 44 , 45 ]. The highest concentration in faeces in our study corresponded to β-carotene and lycopene, which are also generally more abundant in the human diet and blood [ 2 , 46 , 47 ]. The carotenoid concentration in this study was higher than that found in similar volunteers ( n = 101) in a previous study [ 26 ], and higher (more than two times the β-carotene and lycopene levels) than those described in young women ( n = 7) [ 48 ].…”
Section: Discussionmentioning
confidence: 79%
“…The carotenoid concentration in faeces has been used as a non-invasive approach to evaluate carotenoid bioavailability [ 44 , 45 ]. The highest concentration in faeces in our study corresponded to β-carotene and lycopene, which are also generally more abundant in the human diet and blood [ 2 , 46 , 47 ]. The carotenoid concentration in this study was higher than that found in similar volunteers ( n = 101) in a previous study [ 26 ], and higher (more than two times the β-carotene and lycopene levels) than those described in young women ( n = 7) [ 48 ].…”
Section: Discussionmentioning
confidence: 79%
“…One possible explanation is that the bioavailability of carotenoids does not depend solely on physiological mechanisms but can be affected by many other factors, such as gender [32], dietary factors [33], and health status [34]. In support of this premise, one study of Europeans has shown that the bioavailability of α-carotene and β-cryptoxanthin with consideration of eating amount is higher compared to that of β-carotene [35]. Moreover, Britton [36] argued that zeaxanthin is a more effective antioxidant than β-carotene because of its less hydrophobic structure, which can react with free radicals not only in the inner cell membrane but also in the interior aqueous phases.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites such as individual carotenoids, α-tocopherol, 5-MTHF in blood and potassium, and acetate in urine are ubiquitously present in plant origin foods or nature [53,54,73], thus they are not suitable as biomarkers for a specific type of FV. Although papaya is indeed one of the richest sources of β-cryptoxanthin, in a study with 159 Costa Rican adolescents [39], this compound was also found in other orange-or red-colored foods, such as orange, mango, apricot, sweet peppers, and pumpkin [18,74]. Vázquez-Manjarrez et al mentioned that the blood concentration of lycopene is more likely to reflect the intake of tomato products [75].…”
Section: Candidate Biomarkers For Intake Of Specific Fruit and Vegetablementioning
confidence: 99%